2008
DOI: 10.1021/om800127h
|View full text |Cite
|
Sign up to set email alerts
|

Phospha-Scorpionate Complexes by Click Chemistry using Phenyl Azide and Ethynylphosphine Oxides

Abstract: The copper-catalyzed Click reaction of phenyl azide with ethynylphosphine oxides provides new P-substituted triazoles. With tris(ethynyl)phosphine oxide this route affords a versatile scorpionate ligand that coordinates to RhCl 3 as a tripodal N ligand. Upon reduction, the same ligand can act as a P donor to W(CO) 5 . Both coordination modes can be combined, giving access to a bimetallic Mo/W complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 48 publications
1
34
0
2
Order By: Relevance
“…[34][35][36] The OP(Tz Ph ) 3 ligand shows similar features as found in the two crystallographically characterized examples known so far, that is, the RhCl 3 [20] and PtMe 3 [BArF 24 ] [23] complexes of E Ph . Each copper atom is bound by a tridentate OP(Tz Ph ) 3 ligand, and a medial triazolyl nitrogen atom of the other ligand completes the coordination sphere.…”
Section: Scheme 1 Complexation Of E Phmentioning
confidence: 64%
See 3 more Smart Citations
“…[34][35][36] The OP(Tz Ph ) 3 ligand shows similar features as found in the two crystallographically characterized examples known so far, that is, the RhCl 3 [20] and PtMe 3 [BArF 24 ] [23] complexes of E Ph . Each copper atom is bound by a tridentate OP(Tz Ph ) 3 ligand, and a medial triazolyl nitrogen atom of the other ligand completes the coordination sphere.…”
Section: Scheme 1 Complexation Of E Phmentioning
confidence: 64%
“…Both ligand systems and some transition-metal complexes thereof are experimentally known, such as those shown in Figure 2. [9,20] The geometry of the lowest-energy form of the C Me2 ligand is nearly C 3 -symmetric. Evidently, introduction of the methyl groups causes a "ring flip" of two of the pyrazolyl rings of C. Introduction of the phenyl substituent on the triazole rings (E Ph ) has little effect on the geometry of E, which is hardly surprising as the phenyl substituents are positioned far from both the PO apex and the other rings.…”
Section: Calculated Geometries Of the Free Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a stable aromatic heterocycle, the 1,2,3-triazole also contains two nitrogen atoms [N (2) and N(3)] with one pair of non-covalent electrons, indicating both of them can act as donors to coordinate with different metals. 3 Recent research revealed that N(3) atom of 1,2,3-triazole unit did take part in the coordination with metal, 4,5 which was confirmed by single crystal analysis. So 1,2,3-triazole-based ligands from CuAAC reaction have been applied in catalyst, radio-active labeling medicines, organometallics, [5][6][7][8][9][10][11][12] etc.…”
Section: Introductionmentioning
confidence: 85%